The effects of competition and equal treatment laws on the gender wage differential - Doris Weichselbaumer; Rudolf Winter-Ebmer (Johannes Kepler University of Linz, Department of Economics, 2003)
This paper evaluates the impact of economic and legal variables on wage differentials between men and women. Since Becker (1957) economists have argued that competitive markets eliminate discrimination in the long run. On the other hand, practically all countries have enacted some sort of law mandating equal treatment of men and women. This paper uses a new international data set on the gender wage gap, which is constructed via a meta-analysis of existing studies. The findings show that both increased competition and the enactment of equal treatment laws reduce the gender wage gap.
Keywords: J16; J31; J71; 330; Gender wage gap; competition; equal treatment law; Lohndifferenzierung; Geschlecht; Frauenpolitik; Wettbewerb; Schätzung; Welt